2016
DOI: 10.1016/j.pep.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, and characterization of human cystatin C monomers and oligomers

Abstract: Human cystatin C (cysC) is a soluble basic protein belonging to the cysteine protease inhibitor family. CysC is a potent inhibitor of cathepsins - proteolytic enzymes that degrade intracellular and endocytosed proteins, remodel extracellular matrix, and trigger apoptosis. Inhibition is via tight reversible binding involving the N-terminus as well as two β-hairpin loops of cysC. As a significant component of cerebrospinal fluid, cysC has numerous other functions, including support of neural stem cell growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
1
18
0
1
Order By: Relevance
“…In previous work, we developed a simplified affinity chromatography-based protocol for production of recombinant CysC (37). During the routine protein concentration, we discovered CysC contained some oligomers.…”
Section: Ocys Forms Fibrils More Slowly Than Mcysmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we developed a simplified affinity chromatography-based protocol for production of recombinant CysC (37). During the routine protein concentration, we discovered CysC contained some oligomers.…”
Section: Ocys Forms Fibrils More Slowly Than Mcysmentioning
confidence: 99%
“…Recently, we reported on the production and purification of recombinant human CysC. We discovered that a fraction of the protein readily associates into small soluble oligomers (37), raising the question as to whether these oligomers are intermediates to amyloid fibrils. In this report, we test the proposal that CysC forms fibrils by propagated domain-swapping, we investigate the structure of oligomeric CysC, and we probe the role of oligomers in the CysC amyloidogenesis pathway.…”
mentioning
confidence: 99%
“…6, and confirmed at least qualitatively, using Vmax. As detailed by Perlenfein and Murphy [13], the scattering intensity is a linear function of mass concentration and a sixth order function of particle size. Thus, a broader distribution on a logarithmic plot demonstrates a significant increase in particle size.…”
Section: Soluble Aggregatesmentioning
confidence: 95%
“…Moreover, concentration dependent effects become important during ultrafiltration especially on recirculation at higher protein concentrations, where concentration dependent aggregation becomes important. Perlenfein and Murphy [13] reported on the aggregation of human cystatin C as a function of concentration during centrifugal ultrafiltration. From past phenomenological observations, it could be concluded that increased solid-liquid interface contact in tight to medium screen channels, higher wall shear stress during the operation, and concentration dependent effects together may act to produce aggregates and particulates.…”
Section: Effect Of the Screen On Aggregationmentioning
confidence: 99%
See 1 more Smart Citation